Walking the talk: how defining equity turns to action in a research-practice partnership - Hadad, Roxana; Ryoo, Jean; Flapan, Julie; Chan, Sharisa (Frontiers in Education, 2025)
IntroductionThis study examines how a research-practice partnership (RPP) involving university researchers and local education agency leaders across California engaged in the ongoing work of collaboratively defining and operationalizing “equity” in computer science (CS) education implementation. Grounded in Freire’s concepts of praxis, words-as-praxis, and dialog, this qualitative research explores how sustained engagement with defining equity became a transformative practice rather than a preliminary planning activity.MethodsOver 4 years, the RPP iteratively developed three versions of an equity definition, responding to changing socio-political contexts. The RPP expanded from 5 to 17 leaders, ultimately scaling to influence a state-sponsored initiative encompassing 38 county offices of education. Data sources for the study include RPP meeting notes, interviews with RPP members, and analysis of evolving equity documents.ResultsFindings reveal four key themes: (1) productive tensions between CS content focus and equity emphasis that forced deeper examination of assumptions; (2) the necessity of iterative equity definition as an ongoing process responsive to socio-historical contexts; (3) inclusion/exclusion dynamics within the partnership that shaped both representation and understanding; and (4) how collaborative equity definition built capacity for sustained systemic change. Significantly, resistance to equity conversations paradoxically validated the need for sustained dialog, revealing underlying assumptions about CS education’s “neutrality” that required examination.DiscussionThe study demonstrates how collaborative equity definition serves dual functions: developing shared language for collective action while transforming participants’ professional identities and commitments. Participants became leaders of California’s statewide CS education equity initiatives, creating tools and approaches that continue to influence practice years later. This work contributes to research-practice partnership literature by showing how treating equity definition as ongoing praxis—rather than preliminary consensus-building— can create conditions for sustained educational transformation, with implications for STEM education partnerships seeking to center equity while navigating political resistance and changing contexts.